Analisis Daya Dukung Permukiman dan Fungsi Lindung di Koridor Yogyakarta-Temon - Fathurrohmah, Septiana; Yohana Deviyanti Siong; Candra Ragil (ReTII, 2022)
Regional development and population growth in Yogyakarta is happening quite rapidly, with the development of the area around the Yogyakarta-Temon Corridor including the construction of the NYIA (New Yogyakarta International Airport) in Kulon Progo Regency as well as the development planning contained in the DIY Regional Regulation Number 5 of 2019 which states that there is a plan to improve and/ or build a new road, namely the primary arterial road in Yogyakarta-Temon. With this development, it can increase mobility and that will be converted into residential and industrial areas. But on the other side there are also conservation areas that need to be preserved. In achieving the research objectives, several methods were used, namely mathematical statistical data processing and GIS (Geographical Information System) analysis methods to generate spatial information. Then the results of the two carrying capacities are classified by regional typology. The final results of this study indicate that the carrying capacity of settlements in 6 sub-districts is still able to accommodate residents to live properly, while for the carrying capacity of the protected function there are 28 villages classified as medium and 19 villages classified as low. The input for spatial use direction based on regional typology is controlling residential areas, developing transportation network systems, developing infrastructure facilities and maintaining areas that support the carrying capacity of protected functions.